School Social Workers: A Call to Action in Support of Human Rights - Leticia Villarreal Sosa; Raylinn Nuckolls (International Journal of School Social Work, 2018)
The global climate of extremism and direct attacks on marginalized groups such as LGBTQI persons, Muslims, women, immigrants, and refugees creates a need at this critical juncture for school social workers to ground themselves in the international definition of social work, which defines social work as a human rights profession. While there are many challenges to upholding human rights conventions across the world, a human rights framework can assist school social workers in promoting human rights and advocating for vulnerable and marginalized populations. In the context of global migration, children can be especially vulnerable to human rights violations. A human rights approach calls on school social workers to practice in a way that allows for maximum participation of service users in decisions that affect them, addresses power differentials, considers the social context, and privileges an intersectional, strengths based, trauma informed, and recovery oriented approach.
Keywords: human rights; migrant children; UNCRC; school social work; hate crimes